Determinants of Hypertension Occurrence During the Covid-19 Pandemic in the Working Area of the Simpang Tiga Inpatient Health Center, Pekanbaru City in 2022: Determinan Kejadian Hipertensi Selama Pandemi Covid-19 Di Wilayah Kerja Puskesmas Rawat Inap Simpang Tiga Kota Pekanbaru Tahun 2022 - Merry Syafitri; Yuyun Priwahyuni; Mitra Mitra (Badnur Medisa Group, 2022)
Hypertension is a disorder in the blood vessels that causes the supply of oxygen and nutrients carried by the blood to be delayed to the body tissues that need it and blood pressure is more than 140/90 mmHg. The incidence of hypertension during the Covid-19 pandemic in 2021 is quite high in the Puskesmas Inpatient Simpang Tiga with a prevalence of 8.1%. The causes of hypertension are divided into primary and secondary hypertension. The purpose of this study was to determine the determinants of the incidence of hypertension during the covid-19 pandemic in the work area of ​​the Simpang Tiga Inpatient Health Center. This type of research uses quantitative methods with cross sectional design. The population in this study amounted to 3,132 with a sample of 185 respondents using a simple random sampling technique. The study was carried out in the work area of ​​the Simpang Tiga Inpatient Health Center, Pekanbaru City in 2022. The results of this study showed that the proportion of hypertension in the incidence of hypertension during the COVID-19 pandemic was 28.6%. The determinants that have a relationship with the incidence of hypertension are smoking habits (P-value = 0.007) with 95% POR = 2,420 (1,260- 4,647), diet (P-value = 0.000) with 95% POR = 0.219 (0.108-0.443) , physical activity (P-value = 0.006) with 95% POR = 2.981 (1.341-6.625), knowledge (P-value = 0.010) with 95% POR = 2.344 (1.222-4.499), family support (P-value = 0.861 ) with 95% POR = 1.061 (0.549-2.050), and support from health workers (P-value = 0.712) with 95% POR = 0.876 (0.434-1.768). It is recommended for those in charge of health and nutrition promotion to maximize education or socialization related to hypertension counseling to all levels of society who are in the working area of ​​the Inpatient Health Center equally